The Relationship between Perception and Community Willingness in COVID-19 Vaccination in the Working Area in the Nambo Health Center, Kendari City: Perception and COVID-19 Vaccination - Noviati Noviati; Toto Surianto S; La Djabo Buton; Ahmad Mudatsir (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Objectives: The implementation of vaccination is followed by the issuance of various vaccination policies to optimize the achievement of vaccination targets at the national, provincial, and district or city levels. At Nambo Health Center, the number of vaccinations on March 30, 2022, has been recorded as many as 586 people, or 78.13% of the total 1st, 2nd, and 3rd vaccinations. This shows that vaccination achievements are still far from the vaccination target. Methods: As many as 750 people, this condition is due to controversy in the community regarding vaccinations, both related to safety, side effects, and the halalness of vaccines, as well as misinformation obtained by the public, resulting in negative perceptions of the COVID-19 vaccine, which makes them hesitant when they are vaccinated against COVID-19. This type of research is descriptive analytic with a cross-sectional study design. The population in this study was 8,327 people, with a total sample of 99 people using the Cluster Random Sampling technique. Data was analyzed using the chi-square test. Results: The results of the study found that there was a relationship between perception and public willingness to vaccinate against COVID-19 in the working area of the Nambo Health Center, X2 value = 8.523. Conclusion : There is a fairly strong relationship between family support and vaccine availability and there is a weak relationship between public perception and vaccine availability in the working area of the Nambo Health Center. It is hoped that health workers in the working area of the Nambo Health Center Will continue to explain to the public that it is important to follow the COVID-19 vaccination. The dose of COVID-19 vaccination has been properly regulated to form an immune system for every community.